Optical spectrum of HDE 245770 /A0535 + 26/ - R. A. Wade; J. B. Oke (The Astrophysical Journal, 1977)
The global emergence and spread of monkeypox (mpox) have underscored the need for accurate and reliable molecular diagnostic tools. Real-time PCR remains the reference method for detecting mpox virus (MPXV); however, variations among available protocols may affect diagnostic performance. The objective of this study was to compare the diagnostic accuracy of the Centers for Disease Control and Prevention (CDC) of the USA real-time PCR assay with the World Health Organization (WHO) reference molecular protocol, using clinical samples from Ecuador. A retrospective analysis was conducted on 300 specimens from suspected mpox cases, including lesion swabs, vesicular samples, and serum, of which 150 were previously confirmed as MPXV-positive and 150 as MPXV-negative by the WHO assay. DNA was extracted using a standardized protocol, and all samples were tested with the CDC assay. The CDC protocol correctly identified 291 of 300 samples, yielding 141 true positives, 150 true negatives, 9 false negatives, and no false positives. The overall agreement was 97% (95% CI: 94-98), with a sensitivity of 94% (95% CI: 89-97) and a specificity of 100% (95% CI: 98-100). The positive predictive value was 100%, and the negative predictive value was 94% (95% CI: 90-97). The Cohen's kappa coefficient obtained was 0.94 (95% CI: 0.90-0.98). These findings demonstrate that the CDC real-time PCR assay provides high diagnostic accuracy and excellent specificity for MPXV detection compared with the WHO reference protocol, supporting the use of both CDC and WHO real-time PCR assays as reliable diagnostic tools in clinical and surveillance settings.IMPORTANCEThe global emergence and spread of MPXV have underscored the need for accurate PCR diagnostic tools. This is the first study to address a comparison between the PCR protocols for MPXV from the Centers for Disease Control and Prevention (CDC) of the USA real-time PCR assay and the World Health Organization (WHO), two institutions globally acknowledged as references for infectious disease diagnosis. We show that both PCR protocols are very reliable for MPXV diagnosis and could be implemented for any laboratory worldwide indistinctly.